HUBUNGAN ANTARA FAKTOR LINGKUNGAN DAN GANGGUAN MEDIS DENGAN KEJADIAN INSOMNIA PADA REMAJA DI BANGUNTAPAN BANTUL YOGYAKARTA - wahyuningsih, tutik (LPPM Sekolah Tinggi Ilmu Kesehatan Yogyakarta, 2024)
Background: The incidence of insomnia worldwide reached 67% of 1,508 southeast Asians and 23.8% of insomnia occurred in adolescents. In Indonesia, the prevalence rate of insomnia is around 67% while as many as 55.8% have mild insomnia and 23.3% have moderate insomnia. The prevalence of insomnia in Indonesian adolescents reached 38% in urban areas and 37.7% in suburban areas. Yogyakarta City is one of the largest urban areas in Indonesia, which means that adolescents in Yogyakarta City have a high risk of experiencing insomnia. Based on a previous study in 2015 found that as many as 54% of adolescents in Yogyakarta had poor sleep quality and 46% of adolescents had good sleep quality. Based on the results of preliminary studies on adolescents in Banguntapan Bantul Yogyakarta, it is known that 8 adolescents have less than 7-8 hours of sleep per day out of 10 adolescents. Objective: This study aims to determine the correlation between environmental factors and medical disorder factors with the incidence of insomnia in adolescents in Banguntapan Bantul Yogyakarta. Methods: The type of research is quantitative descriptive research with cross sectional design. The population was 480 and the results of the sample calculation were 100. sampling technique using accidental sampling. Data analysis using chi square test. Results: Based on the results of the research conducted, there is a relationship between environmental factors (p = 0.402) with the incidence of insomnia, and there is a relationship between medical disorders (p = 0.000) with the incidence of insomnia. Conclusion: There is a correlation between environmental factors and medical disorders with the incidence of insomnia.